Cost-Effectiveness of Continuous Positive Airway Pressure Therapy in Patients with Obstructive Sleep Apnea-Hypopnea in British Columbia. Issue 3 (2008) - Tan, MCY; Ayas, NT; Mulgrew, A; Cortes, L; FitzGerald, JM; Fleetham, JA; Schulzer, M; Ryan, CF; Ghaeli, R; Cooperx, P; Marra, CA
Abstract : BACKGROUND: Obstructive sleep apnea-hypopnea (OSAH) is a common disorder characterized by recurrent collapse of the upper airway during sleep. Patients experience a reduced quality of life and an increased risk of motor vehicle crashes (MVCs). Continuous positive airway pressure (CPAP), which is the first-line therapy for OSAH, improves sleepiness, vigilance and quality of life. OBJECTIVE: To assess the cost-effectiveness of CPAP therapy versus no treatment for OSAH patients who are drivers. METHODS: A Markov decision analytical model with a five-year time horizon was used. The study population consisted of male and female patients, between 30 and 59 years of age, who were newly diagnosed with moderate to severe OSAH. The model evaluated the cost-effectiveness of CPAP therapy in reducing rates of MVCs and improving quality of life. Utility values were obtained from previously published studies. Rates of MVCs under the CPAP and no CPAP scenarios were calculated from Insurance Corporation of British Columbia data and a systematic review of published studies. MVCs, equipment and physician costs were obtained from the British Columbia Medical Association, published cost-of-illness studies and the price lists of established vendors of CPAP equipment in British Columbia. Findings were examined from the perspectives of a third-party payer and society. RESULTS: From the third-party payer perspective, CPAP therapy was more effective but more costly than no CPAP (incremental cost-effectiveness ratio [ICER] of $3, 626 per quality-adjusted life year). From the societal perspective, the ICER was similar ($2, 979 per quality-adjusted life year). The ICER was most dependent on preference elicitation method used to obtain utility values, varying almost sixfold under alternative assumptions from the base-case analysis. CONCLUSION: After considering costs and impact on quality of life, as well as the risk of MVCs in individuals with OSAH, CPAP therapy for OSAH patients is a highly efficient use of health care resources. Provincial governments who do not provide funding for CPAP therapy should reconsider.